2018
DOI: 10.1103/physreva.98.011802
|View full text |Cite
|
Sign up to set email alerts
|

Generation of frequency sidebands on single photons with indistinguishability from quantum dots

Abstract: Generation and manipulation of the quantum state of a single photon is at the heart of many quantum information protocols. There has been growing interest in using phase modulators as quantum optics devices that preserve coherence. In this Rapid Communication, we have used an electro-optic phase modulator to shape the state vector of single photons emitted by a quantum dot to generate new frequency components (modes) and explicitly demonstrate that the phase modulation process agrees with the theoretical predi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…in. [27][28][29] The difference lies in the introduction of the | G(1) (τ )| 2 term which describes the influence of the driving resonant source. Expressions ( 28) and ( 29) are only valid in the BPP regime.…”
Section: Expression Of the Correlation Functions For The Hom Experimentsmentioning
confidence: 99%
“…in. [27][28][29] The difference lies in the introduction of the | G(1) (τ )| 2 term which describes the influence of the driving resonant source. Expressions ( 28) and ( 29) are only valid in the BPP regime.…”
Section: Expression Of the Correlation Functions For The Hom Experimentsmentioning
confidence: 99%
“…By directly exciting a single QD with cavity-SPDC photons, we have demonstrated the direct coupling between the SPDC photon and a QD. The current work could be immediately extended to show a heralded transfer of a photonic qubit generated from the frequency modulated cavity-SPDC photons using an external modulator [55] to the spin ground states of a charge QD through a direct absorption measurement [12,14]. In addition, such photonic qubits could be teleported to the spin state of a single QD by interfering it with the photons of a spin-photon entangled state [56].…”
Section: Discussionmentioning
confidence: 95%
“…The optical experiment is performed in a dark-field microscopy setup [54,55] where the incident light is focused to a single QD with a high NA (0.65) aspheric lens and the same lens is used to collect the emitted photons. Using a narrowband continuous-wave laser, a single trion state is identified by performing resonance Rayleigh scattering measurement at a fixed non-zero dc bias point [55]. Then the transition energy of the QD is detuned relative to the incident laser by scanning the dc bias voltage while keeping the CW-laser at the fixed frequency.…”
Section: Interfacing Cavity-spdc Photons With a Single Quantum Dotmentioning
confidence: 99%
“…Constructing a flying qubit Hilbert space in frequency domain is bound to boost quantum data communication bandwidth, following the steps of classical optical communication where generally a combination of time-division coding and frequency-division coding is used for high data-rate applications. The possible on-demand generation [15] of single photons with InAs/GaAs QD coupled with the frequency coding [28] we demonstrate here, using off-the-shelf components, makes the platform ideal for long distance and high bandwidth quantum communication. Paudel et al [28] recently demonstrated the preservation of indistinguishability of near-infrared photons emitted by a quantum dot through phase modulation.…”
Section: Introductionmentioning
confidence: 99%
“…Paudel et al [28] recently demonstrated the preservation of indistinguishability of near-infrared photons emitted by a quantum dot through phase modulation. We extend this result and move to a triggered QD system with an emission in the standard telecom 1.55 µm band.…”
mentioning
confidence: 99%